Pearls and Pitfalls of Team Science. (June 2019) - Conn, Vicki S.; McCarthy, Ann Marie; Cohen, Marlene Z.; Anderson, Cindy M.; Killion, Cheryl; DeVon, Holli A.; Topp, Robert; Fahrenwald, Nancy L.; Herrick, Linda M.; Benefield, Lazelle E.; Smith, Carol E.; Jefferson, Urmeka T.; et al.
Formidable health problems are often best addressed by teams of scientists with varied expertise. This diversity among team members and complexities in managing teams can lead to challenges in designing, funding, conducting, and reporting research. Team science difficulties can be addressed by sophisticated planning, frequent reassessment and realignment of team strategies with goals, and consistent transparent communication. This article addresses specific strategies to build and sustain research teams, manage team meetings, strategically develop publications and grants, thrive in the midst of disciplinary and individual team member differences, embrace new ideas and change to maintain creativity, and build future team scientists and projects. The potential value in team science justifies the effort required to build and maintain efficient and effective research teams.